Ecto and Endo Parasites Prevalence in Domestic Chickens in Sulaimani Region: Shadan Hassan Abdullah@ and Aram Ahmad Mohammed - Abdullah, Shadan Hassan (The Iraqi Journal of Veterinary Medicine, 2013)
The study was conducted on 65 local adult chickens (Gallus domesticus) to investigate macro - and microscopically presence of external and internal parasites and their prevalence in Sulaimani region-Kurdistan/Iraq from May to July 2012. Results showed that 90.77 % out of total examined chickens were infested with ecto-parasites, out of that 81.36 % (48/59) were infested with lice such as (Menacanthus stramineus, Goniocotes gallinae, Menopon gallinae, Goniodes gigas, Cuclotogaster heterographus ) and 62.72 (37/59) of it with larval stage of soft tick such as (Argas persicus). Mixed infestations with more than two ecto-parasite species were detected. On the other hand 89.23% out of 65 examined chickens were infected by internal parasites including nematodes and cestodes such as (Heterakis gallinarum which formed 81% and the remains were Ascaridia galli, Cheilospirura hamulosa, Capillaria spp., Raillietina spp., Choanotaenia infundibulum, Amoebotaenia sphenoides, Hymenolepis carioca and Davaniea proglottina).